Pelatihan Penulisan Proposal Penelitian Tindakan Kelas (PTK) Bagi Guru Ekonomi Kabupaten Sidoarjo - Soesatyo, Yoyok; Tjipto Subroto, Waspodo; Canda Sakti, Norida; Edwar, Muhammad; Trisnawati, Novi (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2017)
Writing Training of Class Action Research Proposal (TOD/PTK) was held for the MGMP teachers in Sidoarjo Regency which is located at SMANOR Sidoarjo. The Community Service Activities aims to (1) provide information to the trainees about the basic concept of classrooms action research, the essence of class action research (2) to assign the arranging proposal to all participants; (3) giving guidance to all participants about the review of Class Action Research (PTK). This community service activities research using communicative or speech method at the time of giving materials to the participants, discussion and frequently asked questions and the practice of directly compiling a class action research proposal (PTK) and done by the guidance from PKM team. The results obtained community service activities on the classroom action research proposal writing training give benefit to the MGMP economics teacher at Sidoarno Regency. It is because of all participants now are able to arrange their own proposal of class action research, and it is also procide benefits for teachers to continue on making class action research that can be useful for a teacher's promotion